Accounting and Tax Treatment of Cryptocurrencies: A Systematic Review - Mpanza, Sibonelo Sibahle; Aboluwodi, Damilola; Rajaram, Rajendra (EuroEconomica, 2025)
The emergence of cryptocurrencies as a financial innovation has changed the financial industry and the accounting processes in recent years. The primary aim of this study was to discuss the possible treatment of cryptocurrencies in the context of accounting and taxation. Whilst a significant effort has been made to address the uncertainty of accounting and tax treatment of cryptocurrencies, the study also builds on existing knowledge; little is known about cryptocurrencies and the related implications. The study followed a qualitative approach and used paper analysis to achieve the primary objective. The paper analysis included a systematic review of papers. The study focused on the paper analysis of existing data to refine a conceptual framework. It was found that because of the volatility of cryptocurrencies, the existing measurement models, which are the cost model and fair value model, do not cater to cryptocurrencies. This study addressed the gap between financial information and regulations. These fintech advances do not merely challenge the monetary system but also the regulatory system.